2019
DOI: 10.1002/dta.2561
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in vitro phase I microsomal metabolism of designer benzodiazepines: An update comprising flunitrazolam, norflurazepam, and 4'‐chlorodiazepam (Ro5–4864)

Abstract: The number of newly appearing benzodiazepine derivatives on the new psychoactive substances (NPS) drug market has increased over the last couple of years totaling 23 'designer benzodiazepines' monitored at the end of 2017 by the European Monitoring Centre for Drugs and Drug Addiction. In the present study, three benzodiazepines [flunitrazolam, norflurazepam, and 4′-chlorodiazepam (Ro5-4864)] offered as 'research chemicals' on the Internet were characterized and their main in vitro phase I metabolites tentative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, the newest DBDZ may have high cross-reactivity with common BZD immunoassays, which often do not distinguish between designer and prescribed BZD. Metabolism to licensed BZD, the sale of metabolites of prescribed BZD and the unavailability of confirmatory testing in health care centers pose the risk of an incorrect interpretation of analytical findings [5,127,[155][156][157]. The roles DBZD play in deaths remains poorly understood, and how different pathologists and toxicologists attribute and interpret cause of death is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the newest DBDZ may have high cross-reactivity with common BZD immunoassays, which often do not distinguish between designer and prescribed BZD. Metabolism to licensed BZD, the sale of metabolites of prescribed BZD and the unavailability of confirmatory testing in health care centers pose the risk of an incorrect interpretation of analytical findings [5,127,[155][156][157]. The roles DBZD play in deaths remains poorly understood, and how different pathologists and toxicologists attribute and interpret cause of death is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites can then be identified using high-resolution mass spectrometry (MS) based techniques and nuclear magnetic resonance. HLMs have been used to study the metabolism of clonazolam ( 63 ), diclazepam ( 63 ), deschloroetizolam ( 63 ), etizolam ( 63 ), flualprazolam ( 64 ), flubromazepam ( 63 ), flubromazolam ( 63 , 65 ), flunitrazolam ( 66 ), meclonazepam ( 63 , 67 ), metizolam ( 68 ), nifoxipam ( 63 ) and norflurazepam ( 66 ). Another strategy relies on the analysis of urine samples obtained from a large cohort of users.…”
Section: Designer Benzodiazepinesmentioning
confidence: 99%
“…A striking example is flunitrazolam ( Table VI ), where the in vitro experiments conducted by Moosman et. al ( 66 ) identified hydroxylation reactions that could not be confirmed in vivo in the study of Ameline and colleagues ( 74 ). Conversely, the metabolite 7-acetamidoflunitrazolam could be detected in vivo but not in vitro .…”
Section: Designer Benzodiazepinesmentioning
confidence: 99%
“…15 At present, the exogenous ligand studied mainly includes PK 11195, Ro5-4864, Etifoxine, SSR-180575, ZBD-2, YL-IPA08, AC-5216, DAA-1097, etc. [16][17][18][19] Previous studies have shown that these ligands have regulatory activities in different biological functions. Therefore, TSPO is also considered a potential drug target.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol and porphyrins are endogenous ligands of TSPO and have a high affinity for TSPO 15 . At present, the exogenous ligand studied mainly includes PK 11195, Ro5‐4864, Etifoxine, SSR‐180575, ZBD‐2, YL‐IPA08, AC‐5216, DAA‐1097, etc 16–19 . Previous studies have shown that these ligands have regulatory activities in different biological functions.…”
Section: Introductionmentioning
confidence: 99%